A novel herringbone circularly polarized quasi lumped antenna array - Qasaymeh, Yazeed; Issa, Khaled; Alahmadi, Abdullah; Mohamadariff, Othman (Applied Computational Electromagnetics Society, 2019)
Herein, a series herringbone fed traveling wave quasi-lumped circularly polarized antenna array is presented. The proposed quasi-element antenna comprises a narrow strip inductor parallel to the interdigital capacitor. The inductor was placed at the center finger and shorted across the interdigital capacitor with pad capacitors connected at both ends of the structure. Circular polarization was achieved by feeding the quasi elements at the corners with a 90° phase difference along a travelling wave microstrip feed line. The proposed quasi-lumped element antenna has the potential to realize significant size reductions, and it will ultimately be lightweight, small volume, and inexpensive. The antenna characteristics of the array antenna, including return loss and radiation patterns, were characterized. The size of the antenna structure was 21 mm × 38 mm, allowing for potential use in wireless communication systems that use the 5 GHz ISM band. © ACES